2002
DOI: 10.1016/s1044-0305(01)00367-1
|View full text |Cite
|
Sign up to set email alerts
|

In-source H/D exchange and ion-molecule reactions using matrix assisted laser desorption/ionization Fourier transform ion cyclotron resonance mass spectrometry with pulsed collision and reaction gases

Abstract: Controlled in-source ion-molecule reactions are performed for the first time in an external matrix assisted laser desorption ionization (MALDI) source of a Fourier transform ion cyclotron resonance mass spectrometer. The MALDI source with a hexapole ion guide that was originally designed to incorporate pulsed gas to collisionally cool ions (Baykut, G.;Jertz, R.; Witt, M. Rapid Commun. Mass Spectrom. 2000, 14, 1238 -1247 has been modified to allow the study of in-source ion-molecule reactions. Upon laser desor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 67 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…Recently, Purves et al found four conformers of BK ϩ 2H ϩ ions with a combination of H/D exchange and high-field asymmetric waveform ion mobility spectrometry (FAIMS) [33]. The hydrogen exchange level of BK ϩ 2H ϩ ions formed by MALDI [21] was found to be same as that for BK ϩ 2H ϩ ions formed by ESI, observed in an ICR cell [11].…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Recently, Purves et al found four conformers of BK ϩ 2H ϩ ions with a combination of H/D exchange and high-field asymmetric waveform ion mobility spectrometry (FAIMS) [33]. The hydrogen exchange level of BK ϩ 2H ϩ ions formed by MALDI [21] was found to be same as that for BK ϩ 2H ϩ ions formed by ESI, observed in an ICR cell [11].…”
mentioning
confidence: 93%
“…The hexapole exit potential was set to prevent ions from being transmitted to an FTICR and ions exchanged for periods from zero up to 60 s. Recently, Witt et al described the H/D exchange of several peptide ions in a modified hexapole trap coupled to an ICR cell. The hexapole was used as an ion guide to collisionally cool ions generated by MALDI [21]. Ions were trapped for up to 60 s when D 2 O or CD 3 OD vapor was infused into the trap.…”
mentioning
confidence: 99%
“…H/D exchange in a linear hexapole trap of 10 different peptide ions generated by MALDI, combined with FTMS, was described by Witt, Fuchser, & Baykut (2002). After ions were cooled with Ar, the deuterating agent CD 3 OD or D 2 O was added and ions exchanged for up to 60 sec.…”
mentioning
confidence: 99%
“…The operating principle and conditions of the MALDI part of this combined ion source are very similar to the MALDI source described previously 37,. 39 A significant improvement in the MALDI hardware is the use of the 384‐spot microtiter plate format sample plates, which can be positioned by a computer‐controlled high precision x‐y stage. The insertion of the sample plates into the source occurs through the computer‐controlled vacuum lock.…”
Section: Resultsmentioning
confidence: 99%
“…Pulsing gases into the source is not limited to inert collision gases for cooling the ions during their formation. It is shown that by pulsing reactant gases into this region, ion‐molecule reactions can be observed and studied 39. Another FTICR‐MALDI source desorbing ions into a multipole ion guide using even higher pressures in the MALDI region was developed by O'Connor and Costello 40.…”
mentioning
confidence: 99%